ANALISIS STORE ATMOSPHERE TOKO BUKU GRAMEDIA CABANG PRINGSEWU LAMPUNG - Irianto Loka; Elisabeth Putri Dw Amukti (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2017)
The problem of this research is "Does store atmosphere and quality of service affect consumerbuying interest Gramedia Bookstore in Pringsewu ?. This research tries to know what factors influencingconsumer buying interest in Gramedia bookstore in Pringsewu. The purpose of this study was toanalyze the influence of each variable, store atmosphere (????1), service quality (????2), to consumer buyinginterest (Y).Buying interest is a gauge of opportunity a consumer will buy services or goods. Given themany factors that influence the buying interest, this research will analyze the influence of storeatmosphere and the quality of shop service. The purpose of this research is to know and analyze theinfluence between store atmosphere and service quality store in Gramedia Bookstore.The result of data analysis or regression result shows that simultaneously store atmosphereand store service quality influence buying interest. The magnitude of the determination coefficient(adjusted R square) is 0.953. This means that 95.3% of the dependent variable of consumer buyinginterest can be explained by two independent variables: store atmosphere variables and store servicequality, while the remaining 4.7% of buying interest is explained by variables or other causes outside themodel.